Characteristics and risk factors of bacterial meningitis caused by Streptococcus agalactiae, Streptococcus pneumoniae or Escherichia coli in Guangzhou China from 2015 to 2022 - Chen, Danchun; Tang, Benyu; Li, Ying; Zheng, Kelu; Li, Xiaojing; Chen, Wenxiong; Gao, Fei; Gao, Yuanyuan; Shi, Kaili (Frontiers in Cellular and Infection Microbiology, 2023)
Bacterial meningitis (BM) is an infectious disease with high morbidity and mortality rates in children. Although vaccination has improved prevention of BM, this severe disease continues to cause considerable harm to children across the globe. Several risk factors have been identified for BM, including immune status, age, and sex. However, additional patient and disease information is required in order to better understand the local characteristics, epidemiology and risk factors of BM. Here, we collected information from 252 children with BM in the Guangzhou Women and Children Medical Centre medical record database infected with Streptococcus agalactiae, Streptococcus pneumoniae, or Escherichia coli between May 2015 and May 2022. The three pathogen infected BM cased showed distinct trends during the period, and distribution of three BM pathogens across age groups varied significantly. We reviewed the antimicrobial resistance patterns for each of the pathogens which may direct drug use in BM. Finally, we found blood WBC was a protective factor, while glucose levels in the CFS was risk factor, for the length of hospitalization. Collectively, this study provides multi-parameter characteristics of BM, and potentially guide the drug use.